A rhetorical analysis of health communication in some state of the nation addresses of President Nana Addo Dankwa Akufo-Addo - Nentoola, Dora (University of Cape Coast, 2024)
This study examines the persuasive techniques employed by President Nana Akufo-Addo of Ghana in conveying his health policies to the public. The dataset for the study were qualitative documents retrieved from the official website of the presidency. A rhetorical analysis approach to analyse President Nana Addo Dankwa Akufo-Addo‟s health policies captured in the State of the Nation Addresses from 2017 to 2023. The analysis of the data revealed that President Akufo-Addo used emotional appeals to connect with the public, expressing empathy and solidarity during crises like the COVID-19 pandemic, which strengthened support for his healthcare. Also, the study found that President Akufo-Addo employed logical reasoning and evidence-based arguments to demonstrate the effectiveness of his health policies, presenting concrete examples and future initiatives to appeal to the public's sense of reason. President Akufo-Addo‟s strategic use of kairos to give timely addresses during health crises, such as the COVID-19 outbreak, showcased his leadership and responsiveness, reinforcing the importance of preparedness and effective public health responses. Again, the study found that President Akufo Addo did not have a chronological order of presenting aspects of his addresses. However, he prioritises any issues of great concerns first before others. It is recommended that future research in the area of presidential rhetoric and health communication should consider analysing public reception and perceptions after being exposed to the health policies of President Nana Akufo-Addo. This would help to know the effect that the persuasive techniques employed in the speeches have on the public.
viii,140p;, ill
Keywords: Ethos Health communication Kairos and kronos Logos Pathos Presidential Rhetoric